Competitiveness through Energy Management: Evidence from A Kerala based Agro-Machinery Manufacturing Unit - Manoj, Dr.P.K. (Journal of Contemporary Research in Management (JCRM), 2013)
Agricultural machinery manufacturing industry has got strategic significance in the Indian economy and it has been extended priority status by the Government. But, in the wake of globalization pressures sweeping across the globe, even established players in this industry face considerable challenges, in the form of eroding market shares, dwindling profitability, lowering sales growth rates etc. It has become imperative for any player to draw up well thought-out, meticulously planned business strategies for survival and growth. In the above context, this paper seeks to (i) study the relative competitiveness of KAMCO- a Kerala based agro-machinery manufacturing company vis-Ã -vis major industry players and to trace the major trends over the years, (ii) analyse as to how energy management has helped the company to significantly improve its profitability and competitiveness, and (iii) suggest pragmatic strategies for furtherÂ  enhancing the profitability and competitiveness of the company through cost management.